Prevalence of Hemoglobin-S and Baseline Level of Knowledge on Sickle Cell Disease Among Pregnant Women Attending Antenatal Clinics in Dar-Es-Salaam, Tanzania - Tutuba, Hilda J.; Jonathan, Agnes; Lloyd, William; Luoga, Fredrick; Marco, Emanuela; Ndunguru, Joyce; Kidenya, Benson R.; Makani, Julie; Ruggajo, Paschal; Minja, Irene K.; Balandya, Emmanuel (Frontiers in Genetics, 2022)
Background: Sickle cell disease (SCD) is the single most important genetic cause of childhood mortality globally. Newborn screening (NBS) is the recommended intervention aimed at early identification of babies with SCD and their linkage to care. To ensure success of NBS, pregnant women need to have the required knowledge on SCD and therefore motivation to screen their babies. Objective: The aim of this study was to determine the prevalence of hemoglobin-S and assess the baseline level of knowledge on SCD among pregnant women attending antenatal clinics in urban settings in Dar-es-Salaam, Tanzania. Methods: This cross-sectional study was conducted between August 2020 and February 2021, involving 600 pregnant women at 20–28 weeks of gestation attending antenatal clinics at Buguruni Health Center, Mbagala Hospital, and Sinza Hospital in Dar-es-Salaam, Tanzania. We administered a structured questionnaire to all participants to assess socio-demographic characteristics and baseline level of knowledge on SCD, where those scoring 7 or higher out of 10 questions were considered to have good knowledge. We screened for SCD a total of 300 participants from two centers (Buguruni Health Center and Mbagala Hospital) by using Sickle SCAN point-of-care test (BioMedomics Inc., United States). We used SPSS version 23 to analyze the data. On determining the association between level of knowledge and socio-demographic factors, we used Pearson’s Chi-square and multivariate logistic regression in ascertaining the strength of associations. Results: Of the 600 participants, the majority were of the age between 26 and 35 years (51%), with the parity of 1-3 children (55.8%) and secondary level of education (43%), while 56% were self-employed. Only 14.7% had good knowledge on SCD. The majority of the participants had ever heard of SCD (81.3%), most of them heard from the streets (42.4%), and only 2.4% heard from hospitals. Of all 600 study participants, only 2 (0.3%) knew their SCD status while 7.7% declared having a family history of SCD. A proficient level of knowledge on SCD is associated with a high level of education, occupation, and knowing personal status of SCD. Among 300 participants who were screened for SCD, 252 were Hb-AA (84%), 47 were Hb-AS (15.7%), and 1 (0.3%) was Hb-SS. Conclusion: Despite the high prevalence of hemoglobin-S among pregnant women attending antenatal clinics in urban settings in Tanzania, there is a poor level of knowledge on SCD and personal knowledge of SCD status. Maternal screening and health education on SCD should be included as part of the comprehensive package for health promotion at antenatal clinics.